PENGARUH KARAKTERISTIK CORPORATE GOVERNANCE TERHADAP KECENDERUNGAN PERUSAHAAN KELUARGA MELAKUKAN MANAJEMEN LABA MENGGUNAKAN METODE WarpPLS - Dyah Febriantina Istiqomah; Amelia Ika Pratiwi (Fakultas Ekonomi Universitas 45 Surabaya, 2018)
Agency Conflict or Principal Conflict can be emerge opportunistic profit management behavior. This behavior is avoidable with Good Corporate Governance. The purpose of this study are to identify the effect of Corporate Governance charactertistic to the family company tendency in making profit management by using WarpPLS method. The finding show that there is no found a tendency of the family company to making profit management. Wherease not did not found moderation effect of Corporate Governance on company tendency in making profit management action. However, based on the analysis result found the Corporate Governance effect the profit management behavior indicate the better of company governance, seen from three indicators, that are proportion of independent Commisary and audit Committee, as well audit quality, then the lower practices of profit management in the company. The result show the relationship a Predictor as moderating variable change to be explanatory variable. This result can be expected open the insights of the Indonesia companies to paying attention Corporate Governance applied in the company then profit management behavior can be hazard the company can be avoided. Beside, for further research more focusing on level of family member involvement in running the company because different level of involvement, medium or higher, possibly to influence the tendency of family member to make it or not in profit management making